A RELIGIOUS AND MAGICAL APPLICATION TO HAVE CHILDREN: THE IRK ATMA OCAK (EXAMLE OF TAKMAK VILLAGE-ELIF ISKECE) - Kilic, Sami (Gazi Univ, Turk Kulturu ve Haci Bektas Veli, 2012)
Getting married and having children are a communal and cultural facts. That's why especially in rural areas, there is a big pressure and expectation upon new married couples to have children. Elongation of this period forces especially female childless couples to consult some folk medicine and religious-magical methods apart from methods of medical tretment. The childless women and women whose children die after the birth in Takmak village of Esme-Usak refer to the system of Irk atma to have children and so that they children might live. The irk atma system which is generally based on religious and magical methods and includes the sort of the women desire to have children. The subject of our article includes description and analysis of Elif Iskece's irk atma cap in Takmak village. The datum of the article were obtained via participant observation and in depth interview technique and they were assessed in terms of history of religions by using descriptive method. With this study, we aimed to contribute to the Turkish culture by transferring these applications to the future generations which are held in Takmak village with the irk atma ocagi.
Keywords: Takmak village; The Irkatma ocagi; Elif Iskece; Yunus Dede; Karaca Ahmet Dede; Being bounded to Dede